“Marital Satisfaction And Burnout In Spouses Of Patient With Schizophrenia” - Indu Jacob; Nurnahar Ahmed (Indian Journal of Psychiatric Nursing)
Schizophrenia is a severe mental disorder, characterized by profound disruptions in thinking, affecting language, perception, and the sense of self. The partner diagnosed with schizophrenia, weaves a web of doubt, confusion and chaos in the caregiving spouse. Information from the World Health Organization states that schizophrenia affects about 24 million people across the world, with a worldwide prevalence of about 0.7%. The study aimed to find out marital satisfaction and burnout in spouses of patient with schizophrenia. Materials And Method: A non experimental quantitative approach and descriptive research design was adopted for the present study. Seventy spouses of patients with schizophrenia were selected through purposive sampling technique. The data was collected by using socio demographic data sheet, Locke & Wallace Marital Adjustment Test (MAT) and Oldenburg Burnout Inventory (OLBI). The collected data were systematically coded, computed and analyzed using descriptive and inferential statistics with SPSS 20. Analyses of the data were done in accordance with the specified objectives. Result: The majority respondents had marital satisfaction and lower scores of burnout. The marital satisfaction of spouses of patient with schizophrenia had significant negative correlation with the domains of burnout i.e. exhaustion (r=−0.534, P=0.000) disengagement (r= −0.366, P=0.002).